Nutrition and diet in breast cancer (Texas Journal of Medical Science, 2022)
Breast cancer is the second most common cancer in the world after lung cancer. The urgency of the problem of oncological diseases is determined by a set of social, economic and epidemiological indicators. Among the prevalent oncological diseases worldwide, breast cancer, which is prevalent among women, remains one of the most pressing problems